The role of languages at the University of Malaya - Kim Yok Choi; Jagdish Kaur (Journal of Modern Languages)
The Malaysian Education Policy accords the status of main medium of instruction to Malay and the status of  second most important language to English. While a formalized  bilingual policy is not yet in place, English is used as a medium of instruction for various academic disciplines at the tertiary level. At the University of Malaya, various courses at the undergraduate level at the Faculties of Medicine, Dentistry, Engineering and Law are taught in English. The use of English as a medium of instruction at the postgraduate level is widespread and dissertations at Masters and PhD levels are allowed to be written in Malay or English. This paper reports the outcome of a survey conducted on the use of languages (especially Malay and English) as  mediums of instruction across the 17 faculties, academies and centres of the University of Malaya. The role of these languages in research and administration is also discussed. Questionnaires and interviews with Deans and the teaching staff from the various institutions provided the necessary data to support the contention that bilingualism is practiced to a greater or lesser degree at the University of Malay. The paper also trace the background to the change in policy that now places greater emphasis on the use of English in Malaysian universities.